Does plasma membrane transbilayer asymmetry coupled to lipid nanodomains drive fast kinetics of FGF2 membrane translocation into the extracellular space? - Lolicato, Fabio; Kaur, Manpreet; Knez, Ana Marija; Saleppico, Roberto; Nickel, Walter (Faraday discussions, 2025)
Fibroblast Growth Factor 2 (FGF2) is a potent mitogen secreted from mammalian cells through an unconventional secretory pathway. This process is mediated by direct translocation of FGF2 across the plasma membrane into the extracellular space. It requires several components that are asymmetrically distributed between the two leaflets of the plasma membrane. At the inner plasma membrane leaflet, FGF2 undergoes sequential interactions with the Na,K-ATPase, Tec kinase, and the phosphoinositide PI(4,5)P2. While the Na,K-ATPase, and Tec kinase are auxiliary factors, interactions of FGF2 with PI(4,5)P2 trigger the core mechanism of FGF2 membrane translocation, inducing FGF2-oligomerization-dependent formation of lipidic membrane pores. At the outer plasma membrane leaflet, membrane-inserted FGF2 oligomers are captured and disassembled by Glypican-1 (GPC1), resulting in translocation of FGF2 to the cell surface. In a cellular context, a single FGF2 membrane translocation event occurs within 200 milliseconds. In contrast, in an in vitro system, which uses a fully reconstituted liposomal inside-out system with FGF2 added from the outside and luminal encapsulation of high-affinity heparin molecules, FGF2 membrane translocation takes several minutes. Here, we hypothesize that the observed difference is, at least in part, due to the asymmetrical membrane lipid distribution and the spatial organization of the FGF2 translocation machinery in native plasma membranes. We suggest that the molecular machinery mediating FGF2 membrane translocation assembles in ordered nanodomains, characterized by sphingomyelin (SM), cholesterol and phosphoinositide PI(4,5)P2 coupled together. The transbilayer asymmetry of these lipids likely plays a crucial role in regulating the thermodynamics and kinetics of FGF2-induced membrane pore formation. Therefore, succeeding in reconstituting the FGF2 translocation machinery in artificial membranes with an asymmetric transbilayer distribution of SM, PI(4,5)P2 and other membrane lipids may reveal a direct impact on pore-opening kinetics. Similarly, disrupting lipid asymmetry in cells may significantly impact FGF2 secretion rates, a finding that would underscore the importance of the spatial organization of lipids in membrane dynamics. Testing this hypothesis may advance our understanding of how membrane asymmetry and ordered lipid nanodomains regulate critical biological processes, such as the unconventional secretion of FGF2.
Gesehen am 27.10.2025